2010
DOI: 10.3852/09-198
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the complete mitochondrial genome sequences of the soybean rust pathogensPhakopsora pachyrhiziandP. meibomiae

Abstract: The mitochondrial (mt) genomes of two soybean rust pathogens, Phakopsora pachyrhizi and P. meibomiae, have been sequenced. The mt genome of P. pachyrhizi is a circular 31 825-bp molecule with a mean GC content of 34.6%, while P. meibomiae possesses a 32 520-bp circular molecule with a mean GC content of 34.9%. Both mt genomes contain the genes encoding ATP synthase subunits 6, 8 and 9 (atp6, atp8 and atp9), cytochrome oxidase subunits I, II and III (cox1, cox2 and cox3), apocytochrome b (cob), reduced nicotina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 44 publications
4
20
0
2
Order By: Relevance
“…As shown in Figure 5, Hvcontig_161 (71,379 bp, %GC = 33%) and Hvcontig_171 (45,581 bp, %GC = 35%) cover over 70% of the mitochondrial genome of PGT. We also found that 7 contigs of the HvCat assembly entirely covered the mitochondrial genomes of PGT (79,748 bp) and the soybean rust Phakopsora pachyrhizi (31,825 bp; Stone et al, 2010) (results not shown). From this analysis we estimate that the Hva mitochondrial genome it is at least of the size of the PGT mitochondrial genome.…”
Section: Resultsmentioning
confidence: 63%
“…As shown in Figure 5, Hvcontig_161 (71,379 bp, %GC = 33%) and Hvcontig_171 (45,581 bp, %GC = 35%) cover over 70% of the mitochondrial genome of PGT. We also found that 7 contigs of the HvCat assembly entirely covered the mitochondrial genomes of PGT (79,748 bp) and the soybean rust Phakopsora pachyrhizi (31,825 bp; Stone et al, 2010) (results not shown). From this analysis we estimate that the Hva mitochondrial genome it is at least of the size of the PGT mitochondrial genome.…”
Section: Resultsmentioning
confidence: 63%
“…Particularly, the small scaffold 484 presented a strikingly high sequencing depth. Two genes encoding an ATP synthase F0 subunit and a NADH dehydrogenase subunit presenting strong similarity with resident genes of the soybean rust Phakopsora pachyrhizi mitochondrial genome (Stone et al, 2010) are present on this scaffold. Thus, our analysis identifies a new mitochondrial scaffold that will help in refining the genome assembly.…”
Section: Discussionmentioning
confidence: 99%
“…The intergenic regions amount to 30 % and 27 % in Peltigera membranacea and Peltigera malacea respectively and are rich in simple direct, inverted and tandem repeats which can mediate genome evolution, e.g. by errors in recombination producing duplications, inversions and deletions (Alexander et al 2010;Stone et al 2010).…”
Section: Non-coding Regions: Repeats and Tarsmentioning
confidence: 99%